Power relations in Hospitals. Nurses and immigrant fathers and mothers - Juan Luis González Pascual; Manuel Moreno Preciado (Universidad de Alicante, 2015)
The practice of nursing takes place in the context of healthcare institutions, being the interpersonal relationship the backbone of the practice. In the case of immigrants the goal is to provide culturally competent care. However, the hierarchical and normative hospitals (total institutions) make the relationship between nurses and patients difficult, especially when they come from other cultural backgrounds. The objective of this study is to explore the power relations and to identify barriers in the relationship between nurses- immigrant fathers/mothers due to institutional constraints of the hospital. The ethnographic study collected data through the testimonies of the professionals and the parents of immigrant children and also by observing the practice environments in two public hospitals of average size of the Community of Madrid. The results show that nurses, through the exercise of institutional power, establish with immigrant parents asymmetrical relationships favored by language barriers, prejudice and stereotypes. To provide culturally competent care, you need to overcome institutional and personal barriers and establish dialogic relationships that allow flexible and individualized care, avoiding ethnocentrism.